Differentiating early stage florid osseous dysplasia from periapical endodontic lesions: a radiological-based diagnostic algorithm - Victor Daviet-Noual; Anne-Laure Ejeil; Charles Gossiome; Nathan Moreau; Benjamin Salmon (BMC, 2017)
Abstract Background Osseous dysplasia (OD) is the most common fibro-osseous lesion of the jaw affecting the periapical region. Early stages of OD can resemble periapical radiolucencies, thus mimicking the radiological aspects of an endodontic pathology. Such radiolucent lesions affecting previously decayed or treated teeth are even more complex to interpret. Case presentation The aim of this paper is to report a case-series of representative clinical situations describing the radiological features and illustrating the diagnostic workup of patients with florid osseous dysplasia (FOD). Emphasis is given to the endodontic implications of such periapical bone disease and the complexity of accurate diagnosis in the context of endodontic retreatment. We then propose a practical radiological-based diagnostic algorithm to assist the clinician in the diagnostic of OD periapical lesions. Conclusion Periapical lesions may be confused with bone diseases such as osseous dysplasia, especially in the radiolucent initial stage. Knowledge of clinical features associated with a careful reading of cone beam CT images, such as fine opacities within the hypodense periapical lesion, may help determine the right diagnostic.